The talent development process as enhancing athlete functionality: Creating forms of life in an ecological niche - Rothwell, M.; Davids, K.; Stone, J.; Araújo, D.; Shuttleworth, R. (Talent identification and development in sport. International perspectives, 2021)
In this chapter we elaborate on the idea of talent as athlete functionality and discuss how it can be continuously enhanced in development programs by attention to the socio-cultural-historical constraints of a supportive form of life (Wittgenstein, 1953) in high performance sports organisations. Environmental constraints on the design of skill acquisition and talent development programs have received detailed attention recently, with the form of life concept describing how talent development programs in sport have been shaped in different societies (Rothwell, Davids & Stone, 2018; see also Uehara, Button, Falcous & Davids, in press). A form of life describes the everyday practices of specific groups or organisations and captures how wider social, cultural, and historical constraints shape the expression of inherent values, beliefs, traditions, customs, behaviours, and attitudes. There have been many examples proposed of forms of life in high performance sport, such as Jamaican sprinting (Moore, 2015), East African distance running (Ankersen, 2012), Brazilian soccer (Uehara et al., 2018), Australian Rules football (Browne, Robertson, Sweeting & Davids, 2019; Woods, M cKeown, Shuttleworth, Davids & Robertson, 2019) as well as Finnish winter sports (Forsman et al., 2016).